Immunohistochemical profile of endometrioid adenocarcinomas of various degrees of morphological atypism - Savchenko , P.V.; Shponka , I.S.; Hrytsenko , P.O. (Морфологія / Morphologia / Morfologìâ, 2024)
Topicality. Endometrioid adenocarcinoma of the endometrium is a significant part of malignant neoplasms of the uterine body, which, in turn, are the 2nd most common in menopausal women in 2022, according to the Cancer Registry of Ukraine. The absence of a specific clinical picture, similarity to other variants of adenocarcinoma of the uterine body necessitates the study of histological and immunohistochemical criteria to determine the degree of morphological atypism. Purpose. To improve the differential diagnostic immunohistochemical criteria for the diagnosis of endometrioid adenocarcinoma of the endometrium, using the latest international classification data and taking into account the peculiarities of the diagnostic process in Ukraine. Methods. Retrospective analysis of 61 cases of postoperative material of women diagnosed with "endometrioid adenocarcinoma of the endometrium" for the period from 2021 to 2023 included the assessment of morphological, histological, immunohistochemical features with subsequent statistical processing of the results. Results. The ranking of women with a diagnosis of endometrioid adenocarcinoma of the endometrium by age ranged from 30 to 85 years, the most common diagnosis of "endometrioid adenocarcinoma" is in the menopause and postmenopausal period. Markers p63 (strong connection), p16 (relatively strong connection), p53 (medium strength connection) had a statistically significant relationship for endometrioid adenocarcinoma (p<0.001). There is no relationship between the level of CK20 expression and the degree of morphological atypism. Immunohistochemical profile of endometrioid adenocarcinoma p63 "-" (for grade 1 - "+" in part of cells) / p16 "+" in part of cells (for grade 1 - "-") / p53 "-" / Vimentin "+" / CK7 "+ " / CK20 "-". Conclusion. The necessity of using a panel of cytokeratins 7 and 20, Vimentin, p63, p16, p53 in endometrioid adenocarcinomas of the endometrium to determine the degree of morphological atypism is argued.